Parkinsonism, psychomotor slowing, negative and depressive symptoms in schizophrenia spectrum and mood disorders: exploring their intricate nexus using a network analytic approach - Fritze, Stefan; Brandt, Geva A.; Benedyk, Anastasia; Moldavski, Alexander; Volkmer, Sebastian; Daub, Jonas; Krayem, Maria; Kukovic, Jacqueline; Schwarz, Emanuel; Braun, Urs; Wolf, Robert Christian; Kubera, Katharina Maria; et al. (Schizophrenia bulletin, 2024)
Parkinsonism, psychomotor slowing, negative and depressive symptoms show evident phenomenological similarities across different mental disorders. However, the extent to which they interact with each other is currently unclear. Here, we hypothesized that parkinsonism is an independent motor abnormality showing limited associations with psychomotor slowing, negative and depressive symptoms in schizophrenia spectrum (SSD), and mood disorders (MOD).We applied network analysis and community detection methods to examine the interplay and centrality (expected influence [EI] and strength) between parkinsonism, psychomotor slowing, negative and depressive symptoms in 245 SSD and 99 MOD patients. Parkinsonism was assessed with the Simpson-Angus Scale (SAS). We used the Positive and Negative Syndrome Scale (PANSS) to examine psychomotor slowing (item #G7), negative symptoms (PANSS-N), and depressive symptoms (item #G6).In SSD and MOD, PANSS item #G7 and PANSS-N showed the largest EI and strength as measures of centrality. Parkinsonism had small or no influence on psychomotor slowing, negative and depressive symptoms in SSD and MOD. In SSD and MOD, exploratory graph analysis identified one community, but parkinsonism showed a small influence on its occurrence. Network Comparison Test yielded no significant differences between the SSD and MOD networks (global strength p value: .396 and omnibus tests p value: .574).The relationships between the individual domains followed a similar pattern in both SSD and MOD highlighting their transdiagnostic relevance. Despite evident phenomenological similarities, our results suggested that parkinsonism is more independent of negative and depressive symptoms than psychomotor slowing in both SSD and MOD.